2012
DOI: 10.1016/j.ajhg.2012.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-Function Mutations in HOXC13 Cause Pure Hair and Nail Ectodermal Dysplasia

Abstract: Pure hair and nail ectodermal dysplasia (PHNED) is a congenital condition characterized by hypotrichosis and nail dystrophy. Autosomal-recessive PHNED has previously been mapped to chromosomal region 12q12-q14.1, which contains the type II hair keratin and HOXC clusters. Hoxc13-null mice are known to develop hair and nail defects very similar to those seen in human PHNED. We performed whole-exome sequencing in a consanguineous Chinese family affected by PHNED and identified a homozygous nonsense mutation (c.39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 38 publications
(31 reference statements)
4
64
0
Order By: Relevance
“…It is well recognized that specific gene mutations and altered proteins are linked to specific forms of skin diseases, such as ichthyosis, reflecting abnormal squamous differentiation and acantholytic disorders, including pemphigus with epidermal blistering at different levels. Several genes with elevated expression in skin and specific expression patterns in different epidermal layers have earlier been linked to specific forms of skin disease; e.g., (i) KRT15 (alopecia) (Al-Refu 2012) and COL17A1 (bullous pemphigoid and epidermolysis bullosa) (Powell et al 2005) expressed in the basal layer; (ii) FLG (ichthyosis vulgaris (Thyssen et al 2013), which is expressed in the granular layer; (iii) KLK5 (rosacea) (Meyer-Hoffert and Schroder 2011), which is expressed in stratum corneum; and (iv) HOXC13 (ectodermal dysplasia) (Lin et al 2012), which is expressed in hair follicles. Although specific expression patterns do not per se provide functional data, clues to function and possible involvement in disease are given.…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognized that specific gene mutations and altered proteins are linked to specific forms of skin diseases, such as ichthyosis, reflecting abnormal squamous differentiation and acantholytic disorders, including pemphigus with epidermal blistering at different levels. Several genes with elevated expression in skin and specific expression patterns in different epidermal layers have earlier been linked to specific forms of skin disease; e.g., (i) KRT15 (alopecia) (Al-Refu 2012) and COL17A1 (bullous pemphigoid and epidermolysis bullosa) (Powell et al 2005) expressed in the basal layer; (ii) FLG (ichthyosis vulgaris (Thyssen et al 2013), which is expressed in the granular layer; (iii) KLK5 (rosacea) (Meyer-Hoffert and Schroder 2011), which is expressed in stratum corneum; and (iv) HOXC13 (ectodermal dysplasia) (Lin et al 2012), which is expressed in hair follicles. Although specific expression patterns do not per se provide functional data, clues to function and possible involvement in disease are given.…”
Section: Discussionmentioning
confidence: 99%
“…This abundant expression of keratin 85 can explain the severe hair and nail phenotype that is observed in this disorder. The same phenotypes have recently been associated with mutations in HOXC13, which regulates, directly or indirectly via the FOXN1 transcription factor, hair keratins, keratin-associated proteins and desmosomal cadherins [22]. Similar clinical findings were also observed in a Pakistani family with an autosomal recessive inheritance pattern, but with a relatively mild clinical expression.…”
Section: Keratin Disordersmentioning
confidence: 58%
“…Hoxc13 was reported to be highly expressed in the tail, limbs, and nails in early embryos (95)(96)(97). Hoxc13 deficiency in mice and humans causes external hair loss and nail defects, whereas overexpression of Hoxc13 in mice results in ulceration and alopecia (95)(96)(97)(98)(99)(100). Our studies showed that both HOXA1 and HOXC13 play important roles in YAP-regulated epithelial progenitor cell proliferation.…”
Section: Discussionmentioning
confidence: 71%